Picturing Generosity: Explaining the Success of National Campaigns in the Netherlands - Wiepking, Pamala; van Leeuwen, Marco H.D. (Nonprofit and voluntary sector quarterly, 2013)
In this study, we investigate the success of national campaigns for charitable causes in the Netherlands using historical data from archival sources, including newspapers, and the internet. We describe the 102 national campaigns held in the Netherlands between 1951 and 2011, focusing on uniquely Dutch contextual features such as a society organized along vertical pillars and highly formalized collaboration between international aid organizations. We then formulate and test hypotheses concerning possible explanations for the success of national campaigns as a specific type of fundraising campaign. We focus on the effect of campaigns organized for “innocent” victims, versus campaigns organized for victims of man-made disasters, the effect of media coverage on campaigns, campaign frequency, government contributions, and economic conditions. The results show that campaigns for victims of man-made disasters are less successful. Campaigns organized in periods of fewer competing campaigns and campaigns receiving government support are more successful.